Peran Kepala Sekolah Sebagai Supervisor Klinis Dalam Meningkatkan Kinerja Guru - Titi Hartini (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Clinical Supervision is needed by educators to improve professional teacher performance. Through clinical supervision, school principals can carry out coaching related to increasing the competence of teaching staff in carrying out learning in class. Clinical supervision carried out by the principal at SMP Negeri 1 Cikoneng is carried out through stages which globally consist of pre-observation meetings, classroom observations and return meetings or post-observation. As well as follow-up evaluation. The purpose of this study was to determine the role of the school principal in the implementation of clinical supervision which has an impact on teacher performance in carrying out teaching and learning activities. This study used a qualitative descriptive approach by studying the facts that occurred, data collection techniques were obtained through interviews with school principals and teaching staff. direct observation and documentation study. The research was conducted at SMP Negeri 1 Cikoneng, Ciamis Regency. Improving the performance of teachers at Cikoneng 1 Public Middle School is carried out with various activities, including Supervision of the school principal, Educators are motivated so that supervision activities are the desire and awareness of the teaching staff to improve what they feel still needs to be improved both from making preparations, selecting methods, techniques and learning media, so that the learning process in class is more meaningful and students get a pleasant learning experience. The results of this study include: 1) Implementation of clinical supervision is carried out gradually by the principal at Cikoneng 1 Public Middle School, as a coaching effort for teachers to improve the competence of teaching staff in learning. 2) Principals in carrying out clinical supervision are able to improve teacher performance in learning even better. 3). The principal as a clinical supervisor must understand and have strategies that are able to provide change for educators in teaching and learning activities.